(untitled) (Academic Journal of International University of Erbil, 2025)
This study examines the impact of IFRS 9 adoption, liquidity risk, credit risk, and capital adequacy on banking performance, as measured by Return on Assets (ROA), Tobin's Q (TQ), and Earnings Per Share (EPS), using a panel data regression model with 187 observations from 2014 to 2024. The data is collected from the Iraqi Stock Exchange. The findings show that liquidity risk (LCR, LDR) has a significant impact on profitability and earnings, emphasizing the need for liquidity management in ensuring banking stability. Capital adequacy (CAR, Tier 1 Capital) is critical for market value, however, IFRS 9 adoption has a significant impact on earnings but has little effect on profitability or valuation, indicating that regulatory compliance is primarily concerned with financial reporting. Significantly, credit risk indicators (LLP, NPL) had no significant influence on any performance metric, suggesting that short-term banking performance is more dependent on liquidity and capital sufficiency than credit risk. The study also found that firm-specific factors, particularly Firm Size (FS) and Firm Growth (FG), significantly increase banking performance across all models, implying that larger, growing banks outperform their smaller counterparts. The Hausman test findings endorse the Fixed Effects model for TQ, the Random Effects model for EPS, and the Pooled OLS model for ROA, therefore assuring model robustness. These results underscore the need for banks to maximize liquidity buffers, capital reserves, and risk management frameworks to bolster financial stability and promote long-term development. Policymakers must maintain a balanced regulatory framework that promotes openness and guarantees financial resilience. Subsequent study may investigate macroeconomic factors and the enduring impacts of credit risk on banking performance.